Genetic Predisposition to Colon and Rectal Adenocarcinoma Is Mediated by a Super-enhancer Polymorphism Coactivating CD9 and PLEKHG6 - Ke, Juntao; Tian, Jianbo; Mei, Shufang; Ying, Pingting; Yang, Nan; Wang, Xiaoyang; Zou, Danyi; Peng, Xiating; Yang, Yang; Zhu, Ying; Gong, Yajie; Wang, Zhihua; et al. (Cancer epidemiology, biomarkers & prevention, 2020)
Genome-wide association studies (GWAS) have identified dozens of loci associated with colon and rectal adenocarcinoma risk. As tissue-specific super-enhancers (SE) play important roles in tumorigenesis, we systematically investigate SEs and inner variants in established GWAS loci to decipher the underlying biological mechanisms. Through a comprehensive bioinformatics analysis on multi-omics data, we screen potential single-nucleotide polymorphisms (SNP) in cancer-specific SEs, and then subject them to a two-stage case-control study containing 4,929 cases and 7,083 controls from the Chinese population. A series of functional assays, including reporter gene assays, electrophoretic mobility shift assays (EMSA), CRISPR-Cas9 genome editing, chromosome conformation capture (3C) assays, and cell proliferation experiments, are performed to characterize the variant's molecular consequence and target genes. The SNP rs11064124 in 12p13.31 is found significantly associated with the risk of colon and rectal adenocarcinoma with an odds ratio (OR) of 0.87 [95% confidence interval (CI), 0.82-0.92, = 8.67E-06]. The protective rs11064124-G weakens the binding affinity with vitamin D receptor (VDR) and increases the enhancer's activity and interactions with two target genes' promoters, thus coactivating the transcription of and , which are both putative tumor suppressor genes for colon and rectal adenocarcinoma. Our integrative study highlights an SE polymorphism rs11064124 and two susceptibility genes and in 12p13.31 for colon and rectal adenocarcinoma. These findings suggest a novel insight for genetic pathogenesis of colon and rectal adenocarcinoma, involving transcriptional coactivation of diverse susceptibility genes via the SE element as a gene regulation hub.